A Study of Transient Charactiristics of Wind Power Plant Connected to Electric Power Systems - Trịnh, Trọng Chưởng (Journal of Technical Education Science, 2010)
The power system of Vietnam is in its development phase. Due to the increasing number of new power plants in Vietnam power system such as wind power, the stability of this system has become more complex. This is because of interactions of different power plants and the oscillations of generators and lines. This paper presents the stability of the Ninh Thuan 2015 connected Wind Power Plant (20MW) power system with different short-circuit times on the 22kV line and their impact on the system stability. The Electromagnetic Transient simulator PSCAD/EMTDC 4.2 has been used to carry-out the reported case studies